Feedback and planning workshops with adaptation pioneer households - Maiyo, Nathan; Gichuki, Leah; Kiptoo, Emmaculate; Habermann, Birgit (International Livestock Research Institute, 2025)
The CGIAR Livestock and Climate Initiative feedback workshops took place on 11–13 December 2024 in Bomet and Nandi counties. The workshops, led by the International Livestock Research Institute (ILRI), targeted stakeholders who have been actively involved in the pioneering work on adaptation research. Adaptation pioneer households are positive deviant households or family farms that are more effective at adapting to climate change than others in similar circumstances. The workshops presented findings, shared experiences, identified lessons learned, and discussed next steps in strengthening the Pioneer–Positive Deviance (P–PD) approach and considerations for incoming projects in 2025. Participants included pioneer households, the County Governments of Nandi and Bomet, local implementing partners, farmer cooperatives, private companies, and other interested parties. In total, 76 people attended the Nandi workshop and 50 attended the Bomet workshop, representing 26 pioneer households in Nandi County and 19 in Bomet County.